The impact of the introduction of uniform European collective action clauses on European government bonds as a regulatory result of the European sovereign debt crisis - Nicoletta Layher; Eyden Samunderu (Journal of Risk and Financial Management, 2021)
This paper conducts an empirical study on the inclusion of uniform European Collective Action Clauses (CACs) in sovereign bond contracts issued from member states of the European Union, introduced as a regulatory result of the European sovereign debt crisis. The study focuses on the reaction of sovereign bond yields from European Union member states with the inclusion of the new regulation in the European Union. A two-stage least squares regression analysis is adopted in order to determine the extent of impact effects of CACs on member states sovereign bond yields. Evidence is found that CACs in the European Union are priced on financial markets and that sovereign bond yields do respond to the inclusion of uniform CACs in the European Union.
Keywords: 330; collective action clauses; sovereign debt; bond yields